(untitled) (AYUSHDHARA, 2025)
Acharya Sushruta had described 17 Sarvagata rogas in details, in which, Adhimanth is of four types. Adhi-manth directs extremely churning type of pain. In Adhimanth vyadhi, pain is very severe as the patient feels that his eye is being extracted out and churned along with half of the head. If Abhishyand is not treated properly or neglected. It will lead to Adhimanth. End result of Adhimanth is blindness. Glaucoma is not a single disease but a group of disorders characterized by a progressive optic neuropathy resulting in a characteristics appearance of the optic disc and a specific pattern of irreversible visual field defects that are associated frequently but not invariably with raised intraocular pressure. Panchakarma therapy is useful to manage challenging eye diseases in today’s world. In this case study, a 29 years old female patient came to OPD with the complaints of diminished vision since 2 years and diagnosed with glaucoma and she was using Travopost eye drops for the same. She was treated with Panchtikta kshirbasti, Marsha nasya followed by Tarpan and along with Shiropichu, Anjan and Ashchyotana. Diseases like Adhimanth can be easily managed by Ayurveda chikitsa e.g. Basti karma, Nasya and Netra kriyakalpa. This treatment is also useful in prohibition of further optic nerve damage.